2016
DOI: 10.1123/ijspp.2015-0553
|View full text |Cite
|
Sign up to set email alerts
|

Brief Morning Light Exposure, Visuomotor Performance, and Biochemistry in Sport Shooters

Abstract: The 2 light conditions generated heterogeneous visuomotor and physiological effects in sport shooters. The authors therefore suggest that a single half hour of BL exposure is effective in improving cognitive aspects of performance, but not physical performance. Further research is needed to evaluate BL's impact on biochemical parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Furthermore, elite athletes show better visual abilities than their novice sport mates (Smith, 2016). In this context, some authors have suggested the importance of monitoring visual skills during training periods to increase the performance in sport (Evans, Morjaria, & Powell, 2018;Leichtfried, Hanser, Griesmacher, Canazei, & Schobersberger, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, elite athletes show better visual abilities than their novice sport mates (Smith, 2016). In this context, some authors have suggested the importance of monitoring visual skills during training periods to increase the performance in sport (Evans, Morjaria, & Powell, 2018;Leichtfried, Hanser, Griesmacher, Canazei, & Schobersberger, 2016).…”
Section: Introductionmentioning
confidence: 99%